Navigating dust storms and urban living: an analysis of particulate matter infiltration in Dubai’s residences - Jung, Chuloh; Abdelaziz Mahmoud, Naglaa Sami (Frontiers in Built Environment, 2023)
In response to the growing concern of air pollution in Dubai, this study was undertaken to measure and analyze indoor and outdoor particulate matter (PM) concentrations in residential buildings during the spring dust storm period. The research focused on the infiltration of PM into indoor spaces and its impact on indoor air quality, exploring the relationship between PM particle diameter, building infiltration rates, and the indoor influence of outdoor PM. Conducted in a two-bedroom residential unit near a busy road, the study utilized particle size analysis and the indoor-outdoor (I/O) ratio for measurements. The findings revealed that smaller particles, particularly ultrafine PM2.5, had a more substantial influence on indoor PM concentrations than larger particles. It was noted that buildings with higher infiltration rates, especially those with natural ventilation, were more susceptible to outdoor PM infiltration. Additionally, the study highlighted the significant role of occupant behavior, such as cooking and cleaning, in generating indoor PM. However, further research is necessary to better understand the correlation between architectural characteristics, infiltration rates, and the indoor influence of outdoor PM in residential buildings. The study underscores the importance of improved ventilation systems, raising awareness of indoor air quality, and implementing effective mitigation strategies to reduce indoor air pollution and enhance indoor air quality in urban environments like Dubai. These findings contribute significantly to our understanding of indoor and outdoor PM dynamics, emphasizing the urgent need to address indoor air pollution in urban areas.